The impact of water scarcity on food, bioenergy and deforestation1. (16th April 2018) - Winchester, Niven; Ledvina, Kirby; Strzepek, Kenneth; Reilly, John M.
Abstract : We evaluate the impact of explicitly representing irrigated land and water scarcity in an economy‐wide model with and without a global carbon policy. The analysis develops supply functions of irrigable land from a water resource model for 282 river basins and applies them within a global economy‐wide model. The analysis reveals two key findings. First, explicitly representing irrigated land has a small impact on global food, bioenergy and deforestation outcomes. This is because this modification allows irrigated and rainfed land to expand in different proportions, which counters the effect of rising marginal costs for the expansion of irrigated land. Second, changes in water availability have small impacts on global food prices, bioenergy production, land use change and the overall economy, even with large‐scale ( c . 150 exajoules) bioenergy production, due in part to endogenous irrigation and storage responses. However, representing water scarcity and changes in water availability can be important regionally, with relatively arid areas and/or areas with rapidly growing populations fully exhausting our estimated maximum irrigation capacity that allows for improved irrigation efficiency, lining of canals to limit water loss, and expanding storage to fully capture average annual water flows.